Experimental Investigation of the Interaction between Rising Bubbles and Swirling Water Flow - Tomomi Uchiyama; Shunsuke Sasaki (International Journal of Chemical Engineering)
This study experimentally investigates the interaction between rising bubbles and swirling water flow imposed around the central (vertical) axis of a bubble plume in a cylindrical water tank. Small air bubbles are successively released from the bottom of the tank to generate a bubble plume, and a stirring disc at the bottom of the tank is rotated to impose a swirling water flow around the central axis of the bubble plume. The bubbles disperse further with the increasing rotational speed ω of the stirring disc. Some bubbles shift toward the central axis of the swirling flow when ω is high. The nondimensional swirling velocity of water reduces with increasing bubble flow rate when ω is lower than a certain value. However, it is less affected by the bubbles when ω is higher. The precessional amplitude for the upper end of the vortex core increases due to the presence of the bubbles. With increasing ω, the nondimensional precessional velocity decreases, and the bubble effect also reduces.